Memorandum of Understanding between the George Mason University and BRAC University on Collaboration in academic, professional and research development (2007) - George Mason University; BRAC University (George Mason University and BRAC University, 2013)
This MoU signed Eleventh day of November 2007 between George Mason University having its administrative and educational establishment at Fairfax, Virginia, United States (herein after refined to as George Mason) and BRAC University (herein after referred to as BU) based in Dhaka, Bangladesh.